Patterns of Interaction in Webcam Sex Work: A Comparative Analysis of Female and Male Broadcasters. Issue 6 (3rd June 2018) - Weiss, Benjamin R.
ABSTRACT: This article explores how gender shapes patterns of interaction in webcam sex work. Analysis of 40 hours of cyberethnographic data shows that workers' degree of professionalism, rather than their gender, shapes behavior in webcam sex work. This article identifies three patterns exhibited by both female and male professional broadcasters but not by their less professional counterparts: sharing personal information, deferring to the wishes of clients, and conducting dynamic performances. This article contributes to sex work literature by documenting webcam sex work as a new sector of the sex industry and by reassessing how gender matters in sex work.